FILOSOFI KI HADJAR DEWANTARA TERHADAP PEMBENTUKAN KARAKTER MURID SEKOLAH DASAR: PERSPEKTIF DEEP LEARNING DI ERA DIGITAL - Andi Sukma; Hida Handayani; Musdalifah; Rosita; Burhan; Sundari Hamid (STKIP Subang, 2026)
This study was motivated by the suboptimal implementation of Ki Hadjar Dewantara’s educational philosophy in elementary school learning, particularly in addressing the challenges of the digital era that have contributed to shifts in students’ character values. The purpose of this study was to analyze the relevance of Ki Hadjar Dewantara’s educational philosophy to the character development of elementary school students from the perspective of deep learning in the digital era.This study employed a qualitative approach with a case study design, as it focused on an in-depth investigation of learning practices in elementary schools that implement the philosophical values of Ki Hadjar Dewantara. The research subjects were selected purposively and included school principals and teachers. Data collection techniques consisted of in-depth interviews, observations, and documentation, while data analysis was conducted using thematic analysis through data categorization, pattern identification, and contextual interpretation of learning practices.The findings revealed that the implementation of Ki Hadjar Dewantara’s philosophy in deep learning practices significantly contributed to students’ character development, including independence, responsibility, empathy, and self-awareness. Learning activities that emphasized meaning-making, reflection, and active student engagement enabled these values not only to be understood cognitively but also to be internalized in students’ daily learning experiences.Therefore, the integration of Ki Hadjar Dewantara’s educational philosophy and the deep learning approach serves as an important foundation for developing elementary school students’ character that is humanistic, adaptive, and relevant to the demands of the digital era.